To tell a free story : the first century of Afro-American autobiography, 1760-1865 - Andrews, William L., 1946- (University of Illinois Press, 1986)
The author discusses the writings of Richard Allen, Solomon Bayley, Henry Bibb, Henry Box Brown, John Brown, Leonard Black, William Wells Brown, Lewis Clarke, William Craft, Frederick Douglass, Martin R. Delany, Olaudah Equiano, Moses Grandy, Jacob D. Green, William Grimes, James A.U. Gronniosaw, Briton Hammon, Josiah Henson, Harriet Jacobs, John Jea, Lunsford Lane, Jarena Lee, John Marrant, Solomon Northrup, James W. Pennington, James Robert, Moses Roper, Venture Smith, Austin Steward, Nat Turner, Samuel R. Ward, Booker T. Washington, James Watkins, George White, James Williams, and others.